A systematic review and meta-analysis of health utility values among patients with ischemic stroke - Zhou, Jiting; Wei, Qiran; Hu, Hongfei; Liu, Wei; Guan, Xin; Ma, Aixia; Wang, Luying (Frontiers in Neurology, 2023)
Purpose: Ischemic stroke (IS) has a considerable impact on the health-related quality of life (HRQoL) of patients. A systematic review was conducted to summarize and synthesize the HRQoL reported from IS patients.Methods: An electronic search was performed in PubMed, Web of Science, ScienceDirect, Embase and Cochrane Library databases from inceptionup to February 2022 for studies measuring utility values in IS patients. Basic information of the studies, patient characteristics, measurement of the utility values, and utility values were extracted and summarized. Utility values were pooled according to time of evaluation and disease severity classified with modified Rankin Scales (mRS) scores. Quality of the studies were assessed according to key criteria recommended by the National Institute for Health and Care Excellence.Results: A total of 39 studies comprising 30,853 participants were included in the study. Measured with EQ-5D-3L, tThe pooled utility values were 0.42 (95% confidential interval (CI): 0.13 to 0.71), 0.55 (95% CI: 0.43 to 0.68), 0.65 (95% CI: 0.52 to 0.78), 0.60 (95% CI: 0.43 to 0.78) and 0.67 (95% CI: 0.60 to 0.74) for patients diagnosed with IS within 1 month, 3-month poststroke patients, 6month poststroke patients, 12-month poststroke patients, and 24-month or above poststroke patients. Four studies reported utility values classified by mRS scores where synthesized estimates stratified by mRS scores ranged from 0.91 (95% CI: 0.85 to 0.97) for patients with mRS score of 1 to -0.04 (95% CI: -0.18 to 0.11) for those with mRS score of 5. Gender, poststroke complications, tools for measurement and respondents could influence the reported utility values.. As for the health dimension profiles, Usual Activity was the most impacted dimension while Self-care was the least impacted one.This study indicatedsuggests that the utility values in IS patients kept increasing from stroke onset and became HRQoL among patients with IS relatively stabilized at 6 months poststroke. Healthand utility values decreased significantly as mRS scores increased. These results, which 2 This is a provisional file, not the final typeset article facilitates economic evaluations in utility retrieval and selection. Further exploration was required regarding the factors that affect the HRQoL of IS patients.